KELAYAKAN USAHA TANI PADI GOGO DENGAN POLA PENGELOLAAN TANAMAN TERPADU (PTT) DI KABUPATEN ACEH BESAR, PROVINSI ACEH - Eka Fitria; M. Nasir Ali (Widyariset, 2014)
Aceh is one of the center of rice production areas in Indonesia. Nevertheless, especially there upland, rice productivity is still very low. The purpose of this study is to determine the feasibility of upland rice farming pattern through Integrated Crop Management (ICM). Location for the study in Tubaluy Village, Darul Imarah Sub-District, Aceh Besar, during May–August 2009, is determined purposively. The study is conducted over an upland area of 3.0 ha property of several farmer. The study involves 8 farmers as well. The results shows that adopting four varieties of rice with the application of ICM is worth the effort, amidst the four varieties potentially yield very well (6–7 tonnes/ha) and are more often planted by farmers for their moderate resistance to blast attack. Highest production capability is found in Towuti (6.29 tonnes/ha) with R/C ratio (2.88). With the application of a ICM, break even production (TIP) and breakeven price (TIH) analysis of four varieties tested (Cirata 62.32%, Limboto 61.40%, Situ Bagendit 62.32% and Tuwoti 65.35%) results that the production of those four varieties will not cause loss since any reducing in productivity or prices will not exceed the value of TIP or TIH. It means the four varieties remain profitable to be produced. The development of dryland rice farming can be carried out by improving farmers’ access to resources, capital, technology, market and productivity through innovation and diversification of production. Furthermore, the development can be established by empowering farmers, develop- ing the institutions needed, and encouraging active participation of all stakeholders.